The complete mitochondrial genome sequence of Metzia formosae (Cypriniformes, Cyprinidae). (10th September 2013) - Lin, Hung-du; Lin, Feng-Jiau; Chiang, Tzen-Yuh; Lee, Teh-Wang
Abstract: We determined the complete mitochondrial genome (mitogenome) sequence of Metzia formosae, which is known as an endangered freshwater species in Taiwan and mainland China, with a long polymerase chain reaction (PCR) method. The total length of M. formosae mitogenome is 16, 614 bp, consisting of 13 protein-coding genes, 22 transfer RNAs, 2 ribosomal RNAs genes and a noncoding control region. The overall base composition of M. formosae is 31.39% for A, 25.56% for T, 16.23% for G and 26.82% for C, with a slight AT bias of 56.95%. The molecular data here we presented could play a useful role not only for studying the evolutionary relationships and population genetics of Metzia species, but for practicing conservation on endangered fishes.